Peran Guru PAI dalam Pembelajaran Multikultural: Membangun Kesadaran Toleransi Antarumat Beragama di Sekolah - Ahmad Zidan Hamdani; M. Baihaqi Abdullah; Wiwin Luqna Hunaida (Universitas KH. Abdul Chalim Pacet Mojokerto, 2026)
This study aims to explore the role of Islamic Religious Education (PAI) teachers in multicultural learning and their contribution to fostering interfaith tolerance in schools. This article utilizes library research as its research method by reviewing books, journal articles, policy documents, and previous studies relevant to multicultural education and Islamic pedagogy. Data were analyzed using content analysis to identify key themes and develop an integrated understanding of the challenges, strategies, and factors influencing the role of Islamic Religious Education (PAI) teachers. Findings indicate that teachers face several barriers, including institutional limitations, diverse student backgrounds, and limited opportunities to integrate multicultural values ​​into the curriculum. Despite these challenges, Islamic Religious Education (PAI) teachers strive to promote tolerance through exemplary behavior, open dialogue, and reinforcement of Islamic values ​​that emphasize respect for diversity. The study concludes that Islamic Religious Education (PAI) teachers play a crucial role in establishing an inclusive school climate and fostering students' awareness of tolerance, supported by active collaboration between schools and families.